Finance and Development, September 1974. (Finance and Development; Finance and Development ;, 1974)
This paper examines some dimensions of the problem of income inequality. The conventional approach to income inequality is to define the problem in purely relative terms. A familiar technique for this purpose is to measure inequality by the extent to which the income share of groups of individuals or households differs from their population share. The paper examines the problem in terms of income shares of the lowest 40 percent, the middle 40 percent, and the top 20 percent of households ordinally ranked by income.